(untitled) (Annals of Medical Research, 2023)
Aim: Contrary to the previously held belief that hyperthyroidism may be protective against the development of cancer, a growing number of studies suggest a link between hyperthyroidism and thyroid cancer. The purpose of this study is to investigate the incidence of malignancy in patients undergoing total thyroidectomy for hyperthyroidism with toxic adenoma (TA), toxic multinodular goiter (TMNG), and/or Graves’ disease (GD), and to identify factors predictive of malignancy. Materials and Methods: This is a retrospective study of patients aged 18 years and older who underwent total thyroidectomy for toxic adenoma and toxic multinodular goiter associated with hyperthyroidism and Graves’ disease. Thyroidectomies were performed by a single surgeon at a tertiary teaching hospital between January 2014 and December 2020. Our cohort was divided into two separate groups based on whether the pathology results were malignant or benign. Results: Between January 2014 and December 2020, 199 patients were included, 66.3% were female and the average age was 44.6 years. Hyperthyroidism cases included 52.7% toxic multinodular goiter (TMNG), 9.1% toxic adenoma (TA), and 38.2% Graves’ disease (GD). The cohort revealed a 32.6% thyroid cancer incidence in hyperthyroid patients. The leading malignancy was papillary carcinoma. Hyperthyroidism causes significantly predicted malignancy; TMNG had a 42.8% malignancy rate, compared to 22.4% for GD and 16.3% for TA (p=0.005). Fine needle aspiration biopsy (FNAB) findings were significant for malignancy prediction (p=0.001), with 62.9% malignancy after non-diagnostic FNAB results. Conclusion: The study emphasizes the need for careful consideration of malignancy risk in hyperthyroidism cases. Factors such as FNAB results and the type of hyperthyroidism condition significantly influenced malignancy prediction. The results underscore the necessity for a thorough evaluation of hyperthyroid patients at risk of malignancy.